Potencial agricola del frijol (Phaseolus vulgaris L.) en los paises andinos - Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1980)
Data are given of area planted to beans, production, and yields in the Andean countries during 1964-66, 1974-76, and 1978; production, trade, and consumption during 1963-65 and 1973-75; and production, area, and yield growth rates during 1966-76. Constraints for bean productivity, cropping systems, and the main bean types consumed in the Andean countries are indicated. Finally, the potential of this crop is analyzed and data of land use and population patterns in the Andean countries are included. (CIAT)